DFT study of binding and electron transfer from colorless aromatic pollutants to a TiO2 nanocluster: Application to photocatalytic degradation under visible light irradiation - Oprea, Corneliu I.; Panait, Petre; Gîrţu, Mihai A. (Beilstein Journal of Nanotechnology, 2014)
We report results of density functional theory (DFT) calculations on some colorless aromatic systems adsorbed on a TiO2 nanocluster, in order to explain experimental results regarding the photocatalytic degradation of these pollutants under visible light irradiation. Based on our modeling, we are able to clarify why transparent pollutants can degrade under visible light in the presence of a catalyst that absorbs only in the UV, to explain experimental data regarding differences in the efficiency of the degradation process, and to state the key requirements for effective water-cleaning. For that purpose, we analyze the absorption spectrum of the free and adsorbed molecules, the binding configurations, the matching of the energy levels with the oxide catalyst and the likelihood of the charge-transfer to the substrate. The comparison between several colorless aniline and phenolic systems allows a correlation between the chemical structure and the degradation rate of these pollutants.
Keywords: colorless aromatic pollutants; density functional theory; photocatalytic degradation; titanium dioxide; visible light irradiation